Politeness Phenomena as a Source of Pragmatic Failure in English as a Second Language - Aridah Aridah (TEFLIN, 2001)
Abstract: Language should be learned in the cultural context of its speakÃÂers. This is because the speakers bring an intention in performing a linguistic act. Failure in understanding the intention of the speakers will lead to failure in responding to the intended message and, thus, failure in using the language. The study of how language is used in a particular context or situation is the focus of pragmatics. An important pragmatic issue concerns with politeness, i.e. showing awareness of another persons public self-image. This article highlights the politeness pheÃÂnomena and the degree of success in learning English. The issues disÃÂcussed include the definition of politeness, strategies of politeness, poÃÂliteness in the Oriental cultures, politeness in the context of Indonesian cultures, and the implication of politeness phenomena in the teaching of English.